A handbook on the WTO TRIPS agreement - Taubman, Antony; Wager, Hannu; Watal, Jayashree (Cambridge ; New York : Cambridge University Press, 2012)
"This handbook describes the historical and legal background to the TRIPS Agreement, its role in the WTO and its institutional framework and reviews the following areas: general provisions and basic principles; copyright and related rights; trademarks; geographical indications; patents; industrial designs, layout-designs, undisclosed information and anti-competitive practices; enforcement of IPRs; dispute settlement in the context of the TRIPS Agreement; TRIPS and public health; and current TRIPS issues. It contains a guide to TRIPS notifications by WTO members and describes how to access and make use of the official documentation relating to the TRIPS Agreement and related issues. Furthermore, it includes the legal texts of the TRIPS Agreement and the relevant provisions of the WIPO conventions referred to in it, as well as subsequent relevant WTO instruments"--
Machine generated contents note: 1. Introduction to the TRIPS Agreement; 2. Copyright and related rights; 3. Trademarks; 4. Geographical indications; 5. Patents; 6. Industrial designs, layout-designs of integrated circuits, undisclosed information, anti-competitive practices; 7. Enforcement; 8. Dispute prevention and settlement; 9. TRIPS and public health; 10. Current TRIPS issues; Appendix 1. Guide to TRIPS notifications; Appendix 2. Guide to TRIPS documents; Annex 1. Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS Agreement) 1994; Annex 2. Provisions of the Paris Convention for the Protection of Industrial Property (1967) referred to in the TRIPS Agreement; Annex 3. Provisions of the Berne Convention for the Protection of Literary and Artistic Works (1971) referred to in the TRIPS Agreement; Annex 4. Provisions of the International Convention for the Protection of Performers, Producers of Phonograms and Broadcasting Organisations (The Rome Convention) (1961) referred to in the TRIPS Agreement; Annex 5. Provisions of the Treaty on Intellectual Property in Respect of Integrated Circuits (1989) referred to in the TRIPS Agreement; Annex 6. Declaration on the TRIPS Agreement and Public Health (2001); Annex 7. Decision on Implementation of Paragraph 6 of the Doha Declaration on the TRIPS Agreement and Public Health (2003); Annex 8. Decision on Amendment of the TRIPS Agreement (2005); Annex 9. Decision on Extension of the Transition Period under Article 66.1 of the TRIPS Agreement for Least-Developed Country Members for Certain Obligations with Respect to Pharmaceutical Products (2002); Annex 10. Decision on Extension of the Transition Period under Article 66.1 for Least-Developed Country Members (2005).
Includes index.
Keywords: Pronësia Intelektuale = Intellectual Property; Rregulloret Tregtare = Trade Regulations; LAW / Intellectual Property / General